Analisis Penerapan Algoritma Kriptografi Rivest-Shamir-Adleman (RSA) dan Zero-Knowledge Proof Pada Aplikasi Whatsapp Mod - Andika Abadi Pamungkas; Agung S.Y. Irawan (Peneliti.net, 2023)
With the rapid development of technology and the large amount of digitization in various fields of human life, it is necessary to pay attention to the security and certainty of privacy so that there is no leakage of confidential data, both in the private and governmental domains, especially in Indonesia. In this case cyber-attacks will grow and become more numerous; therefore we need a security principle that can prevent these cyber-attacks, especially in sending something that is sensitive which can be called cryptography. One of the applications that can be implemented regarding this cryptography is the Whatsapp application. WhatsApp claims that the application is safe from data theft and messages being intercepted. However, this is doubtful with the presence of Whatsapp Mod which offers more features than the official application. The security of the modified Whatsapp is questionable, so in this study a test was carried out using the MobSF Framework to find out whether there were security holes that could endanger its users. The results of this research are in the form of a report issued by MobSF regarding the level of danger of the Whatsapp Mod Application. With this research, it is hoped that it will be able to make Whatsapp Mod users aware of the dangers of modified applications and Whatsapp can provide advice and strict action against the Whatsapp Mod developers.